Applicability of the institution of a family foundation in agriculture - Bieluk, Jerzy (Przegląd Prawa Rolnego, 2023)
The purpose of the discussion was to answer the question whether the institution of the family foundation may be used in respect of agricultural activities and applied to the regulation of succession in agricultural holdings. An analysis of the Act on family foundation leads to the conclusion that its provisions facilitate succession and prevent the division of inherited assets. However, the tax provisions concerning the agricultural activities of a family foundation are vague and do not allow a clear conclusion as to whether a family foundation may engage in agricultural activities. The author is inclined to conclude that farming activities should be permitted within a family foundation. However, their undertaking within the framework of a family foundation should, in practice, be in agreement with a suitable individual tax interpretation aimed at protection against tax risks.